Relationship between vastus medialis oblique angle, Lysholm score, isometric quadriceps strength, and Tegner score in anterior cruciate ligament reconstruction patients - dyah paramitha dewi, I Gusti Agung; Adhitya, I Putu Gde Surya Adhitya; Putra, I Putu Yudi Pramana (PT. Kesehatan Gerak Fungsi Tubuh, 2025)
Background: The anterior cruciate ligament (ACL) tear represents a serious sports injury in active individuals. While reconstruction seeks to restore knee stability and quadriceps strength, full recovery of the vastus medialis oblique (VMO) angle is frequently not achieved. This study aimed to investigating the relationship between the vastus medialis oblique angle (VMOA) and Lysholm score with quadriceps isometric strength and Tegner score in patients after ACLR. Methods: This research used a literature review method of seven relevant scientific journals published within the last 10 years (2015–2025). The literature was selected based on strict inclusion and exclusion criteria from reputable scientific databases. These include PubMed, Scopus, Google Scholar, and PEDro using the keyword